'I want this place to thrive': volunteering, co-production and creative labour. - Warren, Saskia (Area (0004-0894), 2014)
Until now geographical research on creative labour has tended to characterise it either in terms of 'hot' jobs in 'buzzing' places or precarious, often poorly paid working conditions. This article argues for a subtler consideration of the complex combination of factors at play within the cultural ecology of art-making. The lure of creative labour has been explained by three key rationales: intrinsic motivators of personal satisfaction and social status; risk-taking; and the challenging, self-affirming nature of creative work. Place-making is advanced here as a fourth rationale for volunteering in creative labour. The co-production of Yorkshire Sculpture Park as an affective, practised and material (art) place is explored through the new concept of embodied and emotional philanthropy. Capturing the unbounded and processual qualities of place-making, this paper provides insights into how volunteers labour beside the artist and paid workers to help co-create an internationally renowned art and environmental attraction. Philanthropy is therefore opened from referring to rich, individualistic donors, to include those who gift time, passion and labour. The paper also argues that volunteering, as a form of gifting, is especially significant during times of economic instability.